Palatability status of the Flora of Koh-e-Safaid Range Upper Kurram Valley, Khyber PakhtunKhwa North West Pakistan - Hussain, Wahid; Badshah, Lal; Shah, Sayed Mahmood; Ullah, Shariat; Ali, Asghar (Ethnobotany Research and Applications, 2023)
Background: The current study was carried out in Upper Kurram, Khyber Pakhtunkhwa, Pakistan from 2015 to 2019. Grazing is the most common of the land uses by domestic and wild animals. Grazing is the most significant biotic stress in terrestrial ecosystem after the fire factor. Objectives: Objectives of the study were; to find out the Palatability status of the Flora of Koh-e-Safaid Range Upper Kurram Valley, KP Pakistan; to record the flora of grazing and browsing livestock preferences in the field. Methodology: The palatability of plant species was recorded by observing the grazing livestock in the field. Cattle were visually observed to determine their preferences. All the information’s were confirmed from local elders. Palatable species were categorized into Highly Palatable (HP), Mostly Palatable (MP), Less Palatable (LP), Rarely Palatable (RP) and Non-Palatable (NP). Results: The current study reported five palatability classes based on their utilization by animals. Highest number of plants fell under the group of highly palatable plants 261 (39.90%) which includes Cynodon dactylon, Dicanthium annulatum, Medicago sativa and Rubus fruticosus. The number of mostly palatable plants were 148 (22.62%) such as Alopecurus agrestis, Brachiaria ramosa, Gagea reticulata, Melica persica, Polypogon viridis. The number of rarely palatable plants were 73 (11.16%) such as Allium griffithianum, Achyranthes aspera, Alteranthera pungens, and Dioscorea deltoidea, while 27 (4.12%) plants were observed less palatable such as Coronopus didymus, Carthamus oxyacantha and Ranunculus afghanicus. A total of 145 (22.17%) plants were observed as non-palatable of which Abies pindrow, Agave americana, Alajja rhomboidea, Cedrus deodara and Hertia intermedia were significant among the non-palatable species. Conclusions: Various factors impact the palatability of plants in different localities of the world. These factors include morphology, phenology, minerals and secondary metabolites in a plant. Like most herbivores, it preferred smaller leaves with a smaller specific leaf area and a higher dry matter content in the leaf. Phenological changes associated with climate change are related to the seasonal availability and palatability of food plants. The presence of minerals like Ca, Mg and K, Fe, Mn, Mg and Ca in different palatable plants in Kurram indicates the reason for their palatable condition. Secondary metabolites such as glycosides, alkaloids, nitrates and others such as oxalate, lectins and tannins have an adverse effect on the taste of plants. Keywords: Palatability, grazing, species, Kurram, Pakistan